The novel male meiosis recombination regulator coordinates the progression of meiosis prophase I. (August 2020) - Li, Miao; Feng, Haiwei; Lin, Zexiong; Zheng, Jiahuan; Liu, Dongteng; Guo, Rui; Li, Junshi; Li, Raymond H.W.; Ng, Ernest H.Y.; Huen, Michael S.Y.; Wang, P. Jeremy; Yeung, William S.B.; et al.
Abstract: Meiosis is a specialized cell division for producing haploid gametes in sexually reproducing organisms. In this study, we have independently identified a novel meiosis protein male meiosis recombination regulator (MAMERR)/4930432K21Rik and showed that it is indispensable for meiosis prophase I progression in male mice. Using super-resolution structured illumination microscopy, we found that MAMERR functions at the same double-strand breaks as the replication protein A and meiosis-specific with OB domains/spermatogenesis associated 22 complex. We generated a Mamerr -deficient mouse model by deleting exons 3–6 and found that most of Mamerr −/− spermatocytes were arrested at pachynema and failed to progress to diplonema, although they exhibited almost intact synapsis and progression to the pachytene stage along with XY body formation. Further mechanistic studies revealed that the recruitment of DMC1/RAD51 and heat shock factor 2–binding protein in Mamerr −/− spermatocytes was only mildly impaired with a partial reduction in double-strand break repair, whereas a substantial reduction in ubiquitination on the autosomal axes and on the XY body appeared as a major phenotype in Mamerr −/− spermatocytes. We propose that MAMERR may participate in meiotic prophase I progression by regulating the ubiquitination of key meiotic proteins on autosomes and XY chromosomes, and in the absence of MAMERR, the repressed ubiquitination of key meiotic proteins leads to pachytene arrest and cell death.